Effects of Drill Point Geometry on Cutting Forces and Torque When Drilling AA1050 - Simoncelli, A. (2025)
Reducing energy consumption in drilling operations is crucial for achieving sustainability goals. A study examined 36 drill bits with different geometries and conditions on AA1050. It assessed thrust forces and torque in two machining conditions (Cmin and Cmax) while considering mesh density, tool geometry, and boundary conditions. The results show that finer mesh models exhibit lower thrust forces, while mass scaling primarily influences torque. The pilot hole configuration decreases force, consistent with experiments. Torque decreases by increasing mesh density, matching with the experimental results. Finally, temperature and chip shape are mesh-dependent, affecting torque and force. As a result, our FEM model effectively predicted thrust force and torque, emphasizing the role of the pilot hole configuration in temperature and plastic strain results.